A method for resource treatment of nitric acid tin stripping waste liquid
By adding sulfuric acid and iron sulfate to the waste liquid of tin stripping nitric acid for distillation, the problem of low recovery efficiency of nitric acid and valuable metals in the prior art is solved, and safe and controllable recycling of nitric acid and efficient recycling of valuable metals are achieved. It has good economic benefits and environmental protection effects.
Patent Information
- Application Number
- CN202210758626.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-06-30
AI Technical Summary
The existing tin stripping waste liquid treatment technology is difficult to effectively recover nitric acid and valuable metals, and there are problems of safety risks and resource waste.
By adding sulfuric acid and iron sulfate to the tin stripping waste liquid of nitric acid, distillation is carried out to form light components nitric acid and heavy components, and the removal of ammonia nitrogen and safe and controllable recovery of nitric acid is achieved. Subsequently, through electrolysis and neutralization treatment, the elemental copper and tin mud are recovered to achieve efficient resource recovery.
It realizes safe and controllable recycling of nitric acid, improves the recycling efficiency of valuable metals, reduces resource waste and treatment costs, and has good economic benefits and environmental protection effects.
Smart Images

Figure CN115161710B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, in particular to a method for resource treatment of nitric acid tin stripping waste liquid. Background Art
[0002] The nitric acid stripping waste liquid contains a lot of ammonia nitrogen impurities. Ammonia nitrogen is enriched when distilling and recovering nitric acid. There are great safety risks in repeatedly distilling and recovering nitric acid, which makes it impossible to effectively recover nitric acid. Valuable metals can only be recovered by alkali precipitation. On the one hand, the nitric acid is wasted; on the other hand, the waste liquid is a nitric acid system, and it is difficult to simply and effectively separate the copper from it by reduction method. Tin hydroxide and copper hydroxide can only be obtained by alkali precipitation, and the product value is low. That is, the existing process can recover some valuable resources, but it has not achieved the maximization of resource recovery benefits.
[0003] The existing nitric acid-based tin stripping treatment technology mainly recovers the valuable metals therein. At most, it can first distill and recover part of the nitric acid (when the ammonia nitrogen is greater than a certain value, it must be neutralized. Generally, the nitric acid recovery rate is 40-60%, and the recovery process has certain safety risks), and use liquid alkali to adjust the pH and precipitate step by step to obtain tin mud and copper mud (if the nitric acid system electrolyzes copper, a large amount of nitrogen oxides will be produced, which poses a great environmental risk) to achieve maximum recovery of resources. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a method for resource treatment of nitric acid tin stripping waste liquid. In the process of distilling nitric acid of the present invention, sulfuric acid + ferric sulfate are added to form an iron-ammonium alum precipitate to achieve the removal of ammonia nitrogen in the distillation process, thereby achieving the safety and controllability of the distillation process of nitric acid.
[0005] The technical solution of the present invention is as follows:
[0006] A method for resource treatment of nitric acid tin stripping waste liquid, the method comprising the following steps:
[0007] (1) adding sulfuric acid and ferric sulfate to the nitric acid tin stripping waste liquid, followed by distillation to form a light component nitric acid and a heavy component, and performing solid-liquid separation on the heavy component to form a supernatant solution and a precipitate;
[0008] Normally, sulfuric acid can only be concentrated to about 70% by distillation at 100-120℃, which meets the disposal requirements. When the metal content in the supernatant is not high, it is reused as sulfuric acid. When the copper + tin + iron content in the supernatant is greater than 20%, subsequent electrolytic neutralization and other operations are carried out.
[0009] The amount of sulfuric acid used is such that the volume ratio of nitric acid tin stripping waste liquid to sulfuric acid is 1:1, and the mass concentration of sulfuric acid is 70%; that is, 1 cubic meter of 70% sulfuric acid is added to 1 cubic meter of nitric acid tin stripping waste liquid; the amount of ferric sulfate used is such that the mass ratio of iron element to ammonia nitrogen element is 4:1-20:1, that is, 4-20g of trivalent iron is added to the solution containing 1g of ammonia nitrogen.
[0010] (2) adding water to dilute the supernatant solution to reduce the acidity, and then performing electrolysis to recover elemental copper;
[0011] The acidity is reduced to 20%, that is, water is added to dilute it 3 to 5 times; the electrolysis conditions are that the cathode material used for electrolysis is stainless steel, and the anode material is ruthenium-coated titanium; the electrolysis time is 24 to 48 hours, the current density is 0.5 to 1A / cm, and the copper ion content after electrolysis is less than 10ppm.
[0012] (3) adding alkali to the solution after electrolysis in step (2) to neutralize it to a pH of 3 to 4, and filtering to obtain a tin mud precipitate and a filtrate A;
[0013] The alkali is one of sodium hydroxide, potassium hydroxide and ammonia water. After neutralization, the corresponding salt solution is obtained, and the corresponding salt (sodium sulfate, potassium sulfate or ammonium sulfate) can be obtained by evaporation and crystallization.
[0014] (4) adding hydrogen peroxide to the filtrate A obtained in step (3) to oxidize the divalent iron to trivalent iron, then adding alkali to form a precipitate, and filtering to obtain a sodium sulfate solution and an iron hydroxide precipitate;
[0015] The ferrous iron content was measured by o-phenanthroline spectrophotometry, and the amount of hydrogen peroxide used was 0.5 to 2 times the molar content of the ferrous iron; the alkali was one of sodium hydroxide, potassium hydroxide, and ammonia water.
[0016] (5) distilling and crystallizing the sodium sulfate solution obtained in step (4) to obtain sodium sulfate crystals; washing the iron hydroxide precipitate obtained in step (4) with water and then dissolving it in sulfuric acid to obtain an iron sulfate solution, which is reused in step (1);
[0017] (6) diluting the precipitate obtained in step (1) with water to form a sulfuric acid solution containing iron, copper, tin and ammonia nitrogen, and then electrolyzing it to recover elemental copper;
[0018] Dilute with water 3 to 5 times; the electrolysis conditions are that the cathode material used for electrolysis is stainless steel, and the anode material is ruthenium-coated titanium; the electrolysis time is 24 to 48 hours, the current density is 0.5 to 1A / cm, and the copper ion content after electrolysis is less than 10ppm.
[0019] (7) adding alkali (ammonia water) to the solution after electrolysis in step (6) to neutralize it to a pH of 3 to 4, and filtering to obtain a tin mud precipitate and a filtrate B;
[0020] (8) adding hydrogen peroxide to the filtrate B obtained in step (7) to oxidize the divalent iron to trivalent iron, then adding alkali to form a precipitate, and filtering to obtain an ammonium sulfate solution and an iron hydroxide precipitate;
[0021] The ferrous iron content was measured by o-phenanthroline spectrophotometry, and the amount of hydrogen peroxide used was 0.5 to 2 times the molar content of the ferrous iron.
[0022] (9) distilling and crystallizing the ammonium sulfate solution obtained in step (8) to obtain ammonium sulfate crystals; washing the iron hydroxide precipitate obtained in step (8) with water and then dissolving it in sulfuric acid to obtain an iron sulfate solution, which is reused in step (1).
[0023] The ferric hydroxide precipitate is washed with water until the content of monovalent metal ions in the precipitate is less than 0.1% (sodium, potassium and ammonium content), and washed with water for multiple times, with the ratio of washing water to ferric hydroxide being 2:1. That is, 1 ton of mud is added with 2 tons of water, stirred and slurried evenly, and then filtered after stirring for two hours.
[0024] The beneficial technical effects of the present invention are:
[0025] The present invention first adds sulfuric acid + ferric sulfate to distill nitric acid, and while obtaining the nitric acid fraction, transfers ammonia nitrogen to the precipitate. This step realizes the triple purposes of recovering nitric acid (resourced nitric acid) + separating ammonia nitrogen (ensuring the safety and controllability of the nitric acid recovery process) + converting the solution from the nitric acid system to the sulfuric acid system (which can achieve subsequent electrolysis to obtain elemental copper); the metal-containing solution is a sulfuric acid solution containing iron, copper and tin, and copper is obtained by electrolysis; the pH is then adjusted to obtain tin mud for sale; iron is washed by precipitation and then dissolved by sulfuric acid to realize the circulation of iron elements. Finally, nitric acid, elemental copper and tin mud products are obtained, and the product value is high and has good economic benefits.
[0026] The present invention realizes the recovery of nitric acid, and the mother liquor sulfuric acid can be reused, which can greatly increase the metal content in the liquid to be neutralized, reduce the free acidity, and reduce the amount of alkali required for neutralization, which has great economic benefits. The copper product is converted from copper hydroxide into electrolytic copper, and the high-value resource of the product is realized through a simple and easy method, which has the potential for industrial promotion.
[0027] The ammonia nitrogen of the present invention can be directly prepared into an ammonium sulfate product by adding ammonia water to neutralize it at the same time, without the need for conventional alkali aeration and then using sulfuric acid to absorb ammonium sulfate, which also shortens the disposal process to a certain extent and reduces the disposal cost. Ferrous sulfate is easily available in industry and non-toxic, and can be recycled and reused without any additional secondary production, that is, when the ammonia nitrogen removal process achieves the above advantages, it does not bring other problems. It can enrich and expand the research and application space and prospects of the iron ammonium alum method. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the processing flow of the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0030] Example 1
[0031] A method for recycling nitric acid tin stripping waste liquid, comprising the following steps:
[0032] The composition of the tin stripping waste liquid is 7172ppm of copper, 23436ppm of tin, 3374ppm of ammonia nitrogen, 267100ppm of nitrate, and the other components are hydrogen ions, that is, the waste liquid is 17% nitric acid + 1.6% copper nitrate + 5.7% tin nitrate + 1.1% ammonium nitrate;
[0033] (1) Add one ton of waste liquid to one ton of 70% sulfuric acid + 54 kg of ferric sulfate (the iron content is about 4 times the ammonia nitrogen content) and stir to dissolve. Evaporate and concentrate at 100° C. and -0.04 MPa for 4 hours to obtain a fraction of nitric acid and a mother liquor (the mother liquor contains a small amount of precipitate). The nitric acid is sold as a product.
[0034] (2) After the mother liquor was allowed to settle, the supernatant was taken out and reused as 70% sulfuric acid; the distillation operation was repeated 7 times, and the distillate nitric acid was collected; the contents of the components in the distillate were shown in Table 1; at this time, the copper, iron and tin contents in the supernatant were greater than 200,000 ppm, and the copper, iron and tin contents in the supernatant after each distillation operation were shown in Table 2; the supernatant was taken out for disposal, and the precipitate produced after each distillation operation was mixed and disposed of; two cubic meters of water was added to one cubic meter of supernatant to dilute it, and at this time, the ammonia nitrogen content in the dilution was about 320 ppm, the copper content was about 16,700 ppm, the tin content was 54,700 ppm, and the iron content was about 1,490 ppm. Stainless steel was used as the cathode and ruthenium-coated titanium was used as the anode. The electrolysis was 24 hours, the current density was 0.5 A / cm, and the copper content in the electrolyte was 3.1 ppm;
[0035] (3) adding 50% liquid caustic soda to the electrolyte to adjust the pH to 3.0, filtering to obtain tin mud, the tin content in the filtrate is 2.3ppm; adding 20kg 30% hydrogen peroxide to the filtrate to react for 1h, and detecting that the divalent iron content in the oxidation solution is 3.5ppm; adding 50% liquid caustic soda to the oxidation solution to adjust the pH to 5-6, filtering to obtain sodium sulfate solution and iron hydroxide precipitate, the iron content in the sodium sulfate solution is 1.4ppm;
[0036] (4) evaporating and crystallizing the sodium sulfate solution to obtain sodium sulfate crystals; washing the ferric hydroxide with water for multiple times to reduce the sodium content in the precipitate to less than 0.1%, and then dissolving it with sulfuric acid to obtain a ferric sulfate solution that is reused for removing ammonia nitrogen;
[0037] (5) One ton of precipitate is diluted with two tons of water. At this time, the ammonia nitrogen content in the dilution is about 14350ppm, the copper content is about 7300ppm, the tin content is 17200ppm, and the iron content is about 27910ppm. Stainless steel is used as the cathode and ruthenium-coated titanium is used as the anode. The electrolysis is for 24 hours, the current density is 0.5A / cm, and the copper content in the electrolyte is 2.7ppm;
[0038] (6) 20% ammonia water was added to the electrolyte to adjust the pH to 3.0, and filter press was performed to obtain tin mud, and the tin content in the filtrate was 1.2 ppm; 600 kg 30% hydrogen peroxide was added to the filtrate to react for 1 hour, and the divalent iron content in the oxidizing solution was detected to be 4.8 ppm; 20% ammonia water was added to the oxidizing solution to adjust the pH to 5-6, and filter press was performed to obtain ammonium sulfate solution and iron hydroxide precipitate, and the iron content in the ammonium sulfate solution was 2.5 ppm; the ammonium sulfate solution was evaporated and crystallized to obtain ammonium sulfate crystals; after the iron hydroxide was washed with water for multiple times, the ammonia nitrogen content in the precipitate was reduced to less than 0.1%, and then it was dissolved in sulfuric acid to obtain an iron sulfate solution that was reused for removing ammonia nitrogen.
[0039] Table 1
[0040]
[0041]
[0042] Note: The fraction produced by distillation is marked as fraction-1, and the supernatant produced is marked as supernatant-1; the subsequent steps are similar; the same below.
[0043] Table 2
[0044] Ammonia nitrogen / ppm Copper / ppm Iron / ppm Tin / ppm Nitrate / ppm Original solution 3374 7172 4.7 23436 267100 Supernatant-1 722 5902 1263 21964 1w-2w Supernatant-2 962 13716 1820 51652 1000-2000 Supernatant-3 842 18547 2475 77863 500-1000 Supernatant-4 1109 25970 2721 96602 <100 Supernatant-5 876 32547 3328 112587 <100 Supernatant-6 743 40387 3576 140204 <100 Supernatant-7 970 49651 4437 163785 <100
[0045] Example 2
[0046] A method for recycling nitric acid tin stripping waste liquid, comprising the following steps:
[0047] The composition of the tin stripping waste liquid is 9347ppm of copper, 47896ppm of tin, 6475ppm of ammonia nitrogen, 297100ppm of nitrate, and the other components are hydrogen ions, that is, the waste liquid is 9.7% nitric acid + 2.1% copper nitrate + 11.9% tin nitrate + 2.1% ammonium nitrate;
[0048] (1) Add one ton of waste liquid to one ton of 70% sulfuric acid + 159 kg of ferric sulfate (the iron content is about 6 times the ammonia nitrogen content) and stir to dissolve. Evaporate and concentrate at 110° C. and -0.06 MPa for 4 hours to obtain a fraction of nitric acid and a mother liquor (the mother liquor contains a small amount of precipitate). The nitric acid is sold as a product.
[0049] (2) After the mother liquor was allowed to settle, the supernatant was taken out and reused as 70% sulfuric acid; the distillation operation was repeated 4 times, and the distillate nitric acid was collected; the contents of the components in the distillate were shown in Table 3; at this time, the copper, iron and tin contents in the supernatant were greater than 200,000 ppm, and the copper, iron and tin contents in the supernatant after each distillation operation were shown in Table 4; the supernatant was taken out for disposal, and the precipitate produced after each distillation operation was mixed and disposed of; two cubic meters of water was added to one cubic meter of supernatant to dilute it, and at this time, the ammonia nitrogen content in the dilution was about 240 ppm, the copper content was about 11,400 ppm, the tin content was about 64,800 ppm, and the iron content was about 13,700 ppm. Stainless steel was used as the cathode and ruthenium-coated titanium was used as the anode. The electrolysis was 36 hours, the current density was 0.8 A / cm, and the copper content in the electrolyte was 2.5 ppm;
[0050] (3) adding 50% liquid caustic soda to the electrolyte to adjust the pH to 3.5, filtering, and obtaining tin mud, the tin content of the filtrate is 3.9 ppm; adding 400 kg 30% hydrogen peroxide to the filtrate to react for 1 hour, and detecting that the divalent iron content in the oxidation liquid is 1.7 ppm; adding 50% liquid caustic soda to the oxidation liquid to adjust the pH to 5-6, filtering, obtaining sodium sulfate solution and ferric hydroxide precipitate, the iron content in the sodium sulfate solution is 5.3 ppm;
[0051] (4) evaporating and crystallizing the sodium sulfate solution to obtain sodium sulfate crystals; washing the ferric hydroxide with water for multiple times to reduce the sodium content in the precipitate to less than 0.1%, and then dissolving it with sulfuric acid to obtain a ferric sulfate solution that is reused for removing ammonia nitrogen;
[0052] (5) One ton of precipitate is diluted with two tons of water. At this time, the ammonia nitrogen content in the dilution is about 15700ppm, the copper content is about 8500ppm, the tin content is 24600ppm, and the iron content is about 28300ppm. Stainless steel is used as the cathode and ruthenium-coated titanium is used as the anode. The electrolysis time is 36h, the current density is 0.8A / cm, and the copper content in the electrolyte is 1.6ppm;
[0053] (6) 20% ammonia water was added to the electrolyte to adjust the pH to 3.0, and filter press was performed to obtain tin mud, and the tin content in the filtrate was 0.9 ppm; 900 kg 30% hydrogen peroxide was added to the filtrate to react for 1 hour, and the divalent iron content in the oxidizing solution was detected to be 6.3 ppm; 20% ammonia water was added to the oxidizing solution to adjust the pH to 5-6, and filter press was performed to obtain ammonium sulfate solution and iron hydroxide precipitate, and the iron content in the ammonium sulfate solution was 6.1 ppm; the ammonium sulfate solution was evaporated and crystallized to obtain ammonium sulfate crystals; after the iron hydroxide was washed with water for multiple times, the ammonia nitrogen content in the precipitate was reduced to less than 0.1%, and then it was dissolved in sulfuric acid to obtain an iron sulfate solution that was reused for removing ammonia nitrogen.
[0054] Table 3
[0055] Ammonia nitrogen / ppm Sulfate / ppm Nitric acid content / % Fraction-1 5.63 none 29.31 Fraction-2 14.56 none 31.57 Fraction-3 13.47 none 28.64 Fraction-4 2.78 none 30.25
[0056] Table 4
[0057] Ammonia nitrogen / ppm Copper / ppm Iron / ppm Tin / ppm Nitrate / ppm Original solution 6475 9347 8.4 47896 297100 Supernatant-1 851 8751 10478 48542 <100 Supernatant-2 976 16159 19861 85426 <100 Supernatant-3 782 28964 28673 131576 <100 Supernatant-4 751 34852 41534 194862 <100
[0058] Example 3
[0059] A method for recycling nitric acid tin stripping waste liquid, comprising the following steps:
[0060] The composition of the tin stripping waste liquid is 8571ppm of copper, 57964ppm of tin, 5743ppm of ammonia nitrogen, 307825ppm of nitrate, and the other components are hydrogen ions, that is, the waste liquid is 11.1% nitric acid + 1.9% copper nitrate + 14.4% tin nitrate + 1.9% ammonium nitrate;
[0061] (1) Add one ton of waste liquid to one ton of 70% sulfuric acid + 235 kg of ferric sulfate (the iron content is about 10 times the ammonia nitrogen content) and stir to dissolve. Evaporate and concentrate at 110° C. and -0.08 MPa for 4 hours to obtain distilled nitric acid and mother liquor (the mother liquor contains a small amount of precipitate). The nitric acid is sold as a product.
[0062] (2) After the mother liquor was allowed to settle, the supernatant was taken out and reused as 70% sulfuric acid; the distillation operation was repeated 3 times, and the distillate nitric acid was collected; the contents of the components in the distillate were shown in Table 5; at this time, the copper, iron and tin contents in the supernatant were greater than 200,000 ppm, and the copper, iron and tin contents in the supernatant after each distillation operation were shown in Table 6; the supernatant was taken out for disposal, and the precipitate produced after each distillation operation was mixed and disposed of; two cubic meters of water was added to one cubic meter of supernatant to dilute it, and at this time, the ammonia nitrogen content in the dilution was about 290 ppm, the copper content was about 8,400 ppm, the tin content was about 54,800 ppm, and the iron content was about 27,500 ppm. Stainless steel was used as the cathode and ruthenium-coated titanium was used as the anode. The electrolysis was 48 hours, the current density was 1 A / cm, and the copper content in the electrolyte was 1.9 ppm;
[0063] (3) adding 50% liquid caustic soda to the electrolyte to adjust the pH to 4, filtering to obtain tin mud, and the tin content in the filtrate is 0.8 ppm; adding 1000 kg 30% hydrogen peroxide to the filtrate to react for 1 hour, and the divalent iron content in the oxidation solution is detected to be 4.1 ppm; adding 50% liquid caustic soda to the oxidation solution to adjust the pH to 5-6, filtering to obtain sodium sulfate solution and iron hydroxide precipitate, and the iron content in the sodium sulfate solution is 3.8 ppm;
[0064] (4) evaporating and crystallizing the sodium sulfate solution to obtain sodium sulfate crystals; washing the ferric hydroxide with water for multiple times to reduce the sodium content in the precipitate to less than 0.1%, and then dissolving it with sulfuric acid to obtain a ferric sulfate solution that is reused for removing ammonia nitrogen;
[0065] (5) One ton of precipitate is diluted with two tons of water. At this time, the ammonia nitrogen content in the dilution is about 14300 ppm, the copper content is about 7800 ppm, the tin content is 27600 ppm, and the iron content is about 30100 ppm. Stainless steel is used as the cathode and ruthenium-coated titanium is used as the anode. The electrolysis is 48 hours, the current density is 1 A / cm, and the copper content in the electrolyte is 0.7 ppm;
[0066] (6) 20% ammonia water was added to the electrolyte to adjust the pH to 4.0, and filter press was performed to obtain tin mud, and the tin content in the filtrate was 1.5 ppm; 1200 kg 30% hydrogen peroxide was added to the filtrate to react for 1 hour, and the divalent iron content in the oxidizing solution was detected to be 7.8 ppm; 20% ammonia water was added to the oxidizing solution to adjust the pH to 5-6, and filter press was performed to obtain ammonium sulfate solution and iron hydroxide precipitate, and the iron content in the ammonium sulfate solution was 4.5 ppm; the ammonium sulfate solution was evaporated and crystallized to obtain ammonium sulfate crystals; after the iron hydroxide was washed with water for multiple times, the ammonia nitrogen content in the precipitate was reduced to less than 0.1%, and then it was dissolved in sulfuric acid to obtain an iron sulfate solution that was reused for removing ammonia nitrogen.
[0067] Table 5
[0068] Ammonia nitrogen / ppm Sulfate / ppm Nitric acid content / % Fraction-1 14.31 none 31.74 Fraction-2 4.52 none 28.46 Fraction-3 5.63 none 29.76
[0069] Table 6
[0070] Ammonia nitrogen / ppm Copper / ppm Iron / ppm Tin / ppm Nitrate / ppm Original solution 5743 8571 0.47 57964 307825 Supernatant-1 1057 9057 24785 54756 <100 Supernatant-2 796 15764 60479 114985 <100 Supernatant-3 807 25793 82476 167824 <100
[0071] Comparative Example 1
[0072] The composition of the tin stripping waste liquid is 7172ppm copper, 23436ppm tin, 3374ppm ammonia nitrogen, 267100ppm nitrate, and the other components are hydrogen ions, that is, the waste liquid is 17% nitric acid + 1.6% copper nitrate + 5.7% tin nitrate + 1.1% ammonium nitrate; one part of the waste liquid is added with one part of 70% sulfuric acid and stirred to dissolve, and evaporated and concentrated at 100°C and -0.04MPa for 4h to obtain distilled nitric acid and mother liquor, the nitric acid is sold as a product, and the mother liquor is beaten out and reused as 70% sulfuric acid; the distillation operation is repeated 7 times, and the mother liquor is beaten out for disposal; the content of each component in the mother liquor is shown in Table 7.
[0073] Table 7
[0074] Ammonia nitrogen content / ppm Iron distillation Direct distillation Original solution 3374 3374 Mother liquor-1 722 2817 Mother liquor-2 962 6310 Mother liquor-3 842 9162 Mother liquor-4 1109 13475 Mother liquor-5 876 14758 Mother liquor-6 743 24756 Mother liquor-7 970 29756
[0075] It can be found that ammonia nitrogen is significantly enriched in the mother liquor of the sample without adding ferric sulfate, but not significantly enriched in the mother liquor of the sample with adding ferric sulfate.
Claims
1. A method for recycling nitric acid tin stripping waste liquid, characterized in that: The method comprises the following steps: (1) adding sulfuric acid and ferric sulfate to the nitric acid tin stripping waste liquid, followed by distillation to form a light component nitric acid and a heavy component, and performing solid-liquid separation on the heavy component to form a supernatant solution and a precipitate; (2) adding water to dilute the supernatant solution to reduce the acidity, and then performing electrolysis to recover elemental copper; (3) adding alkali to the solution after electrolysis in step (2) to neutralize it to a pH of 3 to 4, and filtering to obtain a tin mud precipitate and a filtrate A; (4) adding hydrogen peroxide to the filtrate A obtained in step (3) to oxidize the divalent iron to trivalent iron, then adding alkali to form a precipitate, and filtering to obtain a sodium sulfate solution and an iron hydroxide precipitate; (5) distilling and crystallizing the sodium sulfate solution obtained in step (4) to obtain sodium sulfate crystals; washing the iron hydroxide precipitate obtained in step (4) with water and then dissolving it in sulfuric acid to obtain an iron sulfate solution, which is reused in step (1); (6) diluting the precipitate obtained in step (1) with water to form a sulfuric acid solution containing iron, copper, tin and ammonia nitrogen, and then electrolyzing it to recover elemental copper; (7) adding alkali to the solution after electrolysis in step (6) to neutralize to a pH of 3 to 4, and filtering to obtain a tin mud precipitate and a filtrate B; (8) adding hydrogen peroxide to the filtrate B obtained in step (7) to oxidize the divalent iron to trivalent iron, then adding alkali to form a precipitate, and filtering to obtain an ammonium sulfate solution and an iron hydroxide precipitate; (9) distilling and crystallizing the ammonium sulfate solution obtained in step (8) to obtain ammonium sulfate crystals; washing the iron hydroxide precipitate obtained in step (8) with water and then dissolving it in sulfuric acid to obtain an iron sulfate solution, which is reused in step (1).
2. The method according to claim 1, characterized in that: In step (1), the amount of sulfuric acid is such that the volume ratio of the nitric acid tin stripping waste liquid to sulfuric acid is 1:1; the mass concentration of sulfuric acid is 70%; and the amount of ferric sulfate is such that the mass ratio of the iron element to the ammonia nitrogen element is 4:1 to 20:
1.
3. The method according to claim 1, characterized in that In step (2), the acidity is reduced to 20%, that is, water is added to dilute it 3 to 5 times; the electrolysis conditions are that the cathode material used for electrolysis is stainless steel, and the anode material is ruthenium-coated titanium; the electrolysis time is 24 to 48 hours, the current density is 0.5 to 1 A / cm, and the copper ion content after electrolysis is less than 10 ppm.
4. The method according to claim 1, characterized in that In step (3), the base is one of sodium hydroxide, potassium hydroxide and ammonia water.
5. The method according to claim 1, characterized in that In step (4), the ferrous iron content is measured by o-phenanthroline spectrophotometry, and the amount of hydrogen peroxide used is 0.5 to 2 times the molar content of the ferrous iron; and the alkali is one of sodium hydroxide, potassium hydroxide, and ammonia water.
6. The method according to claim 1, characterized in that In step (6), water is added to dilute 3 to 5 times; the electrolysis conditions are that the cathode material used for electrolysis is stainless steel, and the anode material is ruthenium-coated titanium; the electrolysis time is 24 to 48 hours, the current density is 0.5 to 1 A / cm, and the copper ion content after electrolysis is less than 10 ppm.
7. The method according to claim 1, characterized in that In step (7), the base is aqueous ammonia.
8. The method according to claim 1, characterized in that In step (8), the ferrous iron content is measured by o-phenanthroline spectrophotometry, and the amount of hydrogen peroxide used is 0.5 to 2 times the molar content of the ferrous iron.
9. The method according to claim 1, characterized in that: In step (9), the iron hydroxide precipitate is washed with water until the content of monovalent metal ions in the precipitate is less than 0.1%; the washing is repeated multiple times, and the ratio of washing water to iron hydroxide is 2:1.
Citation Information
Patent Citations
Total recycling method of PCB (printed circuit board) nitric acid type tin-lead stripping waste liquid
CN102115890A
Method for treating high-concentration ammonia nitrogen waste water by utilizing ferric sulfate
CN102139944A